2023
DOI: 10.3390/brainsci13030517
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Using Virtual Reality on Thai Word Order Learning

Abstract: Thai has its own unique spelling system and grammatical rules. Its word order is quite different from that of Mandarin and English, thus making it more difficult for students in Taiwan to learn. Past studies also point out that learning word order is one of the most difficult aspects when learning foreign languages. As science and technology advance, emerging technologies have been widely applied in foreign language learning. This research aims to explore the effect of using a multi-language VR learning assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Generally speaking, test anxiety impedes performance achievement. It was found negatively related to learning retention and task value ( Watthanapas et al, 2023 ). Ma et al (2022) ’s study also found test anxiety levels were significantly related to psychiatric traits, students with greater mood swings were prone to greater test anxiety.…”
Section: Theory Background and Literature Reviewmentioning
confidence: 99%
“…Generally speaking, test anxiety impedes performance achievement. It was found negatively related to learning retention and task value ( Watthanapas et al, 2023 ). Ma et al (2022) ’s study also found test anxiety levels were significantly related to psychiatric traits, students with greater mood swings were prone to greater test anxiety.…”
Section: Theory Background and Literature Reviewmentioning
confidence: 99%